E-Banking: Digital Gaps in India - Agrawal, Bindu (Gyan Management Journal, 2017)
Banks have changed their way of operations due to advent of internet in banking institutions. But still the concept of e banking is not much adopted by the Indian banking customers. This paper will try to know the factors and reasons for slow adoption of e banking as compared to developed countries. In India the endorsement of £-Banking is very low as 70 percent population belongs to rural areas and 30 percent reside in urban. Our Government is taking new initiatives to make India digitally connected but still there are some ground realities for delay in the process. E Banking is likely to bring host opportunities as well as poses new challenges for authorities in regulating and supervising the financial system and in designing and implementing the macroeconomic policy. This paper aims to present Emerging £-Banking opportunities & challenges in India.
Keywords: E Banking; Challenges; Opportunities; Emerging